Development of Intermittent Fasting Track application system: Pembangunan sistem aplikasi Intermittent Fasting Track - Zakaria, Nuraida Amirah; Zainal, Nurezayana (Applied Information Technology And Computer Science, 2022)
Intermittent fasting or "Intermittent Fasting (IF)" is a way of eating between fasting and eating according to the schedule. Research results show that intermittent fasting (IF) is an effective way to lose weight. Intermittent fasting practitioners record their fast tracking in a book or on paper. To make it easier for practitioners of the IF diet, the IF application has been developed to help intermittent fasting practitioners track their fasting journey. This IF application offers several fasting plans according to the amount of fasting that can be used for users of the IF application. The app also allows users to refer to the food calorie menu provided for the menu for breaking fast. The prototype model was used as a guide in developing this project. Meanwhile, system development is done using Android Studio and the use of Java as one of the programming scripts. At the end of the project, a mobile application was developed consisting of a history log module to view the history of intermittent fasting trips. In short, this proposed system is expected to help practitioners of this intermittent fasting diet pattern record their fasting journey. Therefore, through the development of this intermittent fasting application, the community in the present era is able to adopt a healthy lifestyle by practicing this intermittent fasting and eating pattern.